2003
DOI: 10.1508/cytologia.68.83
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype Evolution in the Shrews, Crocidura and Suncus (Soricidae, Insectivora).

Abstract: Chromosomes of the Indian taxon of Crocidura horsfieldi, the Indian house shrew, Suncus murinus and the pigmy shrew, S. etruscus are analysed. The karyotype of C. horsfieldi, has 2nϭ38 and is compared with the karyotypes of other species of Crocidura. The house shrew, S. murinus has a general karyotype with 2nϭ40 and the variant karyotypes have 2nϭ30, 31, 32, and 37. The karyotype of the pigmy shrew, S. etruscus consists of 42 chromosomes. The karyotypes of Crocidura, the general karyotype of S. murinus and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The primary assembly was manually curated, correcting 212 missing or missed joins, removing 28 sequences representing false haplotypic duplication, and assigning 99.9% of the sequence to 22 chromosomes, including X and Y. This karyotype was consistent with prior cytological studies 16 – 18 . The resulting reference assembly was highly contiguous, with scaffold N50 of 132 Mbp and contig N50 of 5 Mbp.…”
Section: Background and Summarymentioning
confidence: 87%
“…The primary assembly was manually curated, correcting 212 missing or missed joins, removing 28 sequences representing false haplotypic duplication, and assigning 99.9% of the sequence to 22 chromosomes, including X and Y. This karyotype was consistent with prior cytological studies 16 – 18 . The resulting reference assembly was highly contiguous, with scaffold N50 of 132 Mbp and contig N50 of 5 Mbp.…”
Section: Background and Summarymentioning
confidence: 87%
“…Karyological examination of these species including banding techniques such as G-band karyotypes is desired to be performed. More studies should also be focused on 2n = 38 and FN = 48 karyotype found in Indian C. horsfieldii (Krishna Rao and Aswathanarayana 1978;Aswathanarayana 2003).…”
Section: Unsolved Questionsmentioning
confidence: 99%